Early infantile epileptic encephalopathy type 16: the new clinical and genetic variant of TBC1D24 gene mutation - A. A. Kholin; I. D. Fedonyuk; O. P. Dovelman; N. N. Zavadenko; T. V. Kozhanova; E. A. Kholina; G. Sh. Khondkarian; E. S. Il`ina (Эпилепсия и пароксизмальные состояния, 2020)
Objective: to analyse the clinical and neurophysiological data from a case of early infantile epileptic encephalopathy type 16 in a child with homozygous mutation in TBC1D24 gene.Material and methods. Female child M. aged 1 year and 2 months, with identified mutations in TBC1D24 gene was examined. The whole exome sequencing was performed (Next Generation Sequencing with the Illumina HiSeq 1500 platform, USA). Dynamic video-EEG monitoring was conducted with a “Encephalan-Video” RM-19/26 instrument (“Medicom MTD”, Russia).Results. According to the patient history, on the 22nd day of life, the child developed vocalisms with tonic tension of the limbs. At her 2 months of life, focal myoclonia and myoclono-clonies were noted; at her 4 months – return of tonic seizures with vocalisms followed by eyelid myoclonus, perioral myoclonus, ophthalmoclonia, alternating hemiconvulsions and tonic-clonic seizures. The family history of epilepsy was negative; the parents denied any consanguinity, but admitted a chance of being distant relatives. Neurological examination revealed hypotonic-astatic syndrome and psycho-motor retardation. A video EEG monitoring test detected multiple EEG negative multifocal myoclonic episodes in combination with dystonic hyperkinesia and motor automatism. Although typical epileptiform spike-wave discharges were rare, a focus of low-index spike-wave complexes was identified in the left temporal zone. Therapy with valproates, barbiturates and levetiracetam did not produce any significant effect but benzodiazepines (clonazepam) caused a moderate improvement; a switch to clobazam therapy was then recommended. This case of inherited developmental and epileptic encephalopathy was defined as early infantile epileptic encephalopathy type 16 (OMIM#615338) with autosomal recessive inheritance associated with a previously not described homozygous mutation of the TBC1D24 gene, chr:16:2546775 A>C that caused Tyr209Ser amino acid substitution. Pre-conception testing of the TBC1D24 gene under the IVF condition is recommended to the parents.Discussion. Since 2010, a few variants of early infantile epileptic encephalopathy type 16 caused by homozygous mutation of the TBC1D24 gene have been described in the literature. This clinical case is closer to progressive myoclonic epilepsy with dystonia (PMED), which indicates the nosological autonomy of this form of epilepsy.Сonclusion. Children with pharmacoresistant epilepsy and epileptic encephalopathies, as well as those with unusual course of these diseases need genetic assessment with the new generation exom sequencing techniques – such as the “hereditary epilepsy” panel, as well as clinical and full-exom sequencing.All authors contributed equally to this publication.